Profile of Student Problem Solving Skills Using Discovery Learning Model with Cognitive Conflict Approach - Bahtiar Bahtiar; Ibrahim Ibrahim; Maimun Maimun (Jurnal Penelitian Pendidikan IPA, 2022)
Instruction that focuses on remembering and understanding domains become one of the factors causing students' low ability on problem-solving skill (PSS) in physics. Discovery learning with a cognitive conflict approach becomes one of the solutions to solve this problem. This research aims at finding students' problem-solving skill improvement through discovery learning using the cognitive conflict approach. This research is a Research and Development. The lesson plan that has been developed was widely tried out in the two classes. Data collection of such improvement used to pretest and posttest result on problem-solving skill. The problem-solving indicators applied in this research refer to Docktor & Heller's indicator (2009), such as problems identification, physics description, and specific application of physics, mathematical procedure, and logical conclusion. Based on the N-gain analysis result, it was found that discovery learning using the cognitive conflict approach can improve students' problem skills. Moreover, the N-gain test result on every sub-material work, energy, work and energy conversion, and conservation of energy laws were included in the moderate and high improvement category. Likewise, every problem-solving skill indicator was included in moderate and high improvement categories.